Accretion vs. colliding wind models for the gamma-ray binary LS I +61 303: an assessment - Romero, Gustavo Esteban (2007)
Context. LS I +61 303 is a puzzling Be/X-ray binary with variable gamma-ray emission up to TeV energies. The nature of the compact object and the origin of the high-energy emission are unclear. One family of models invokes particle acceleration in shocks from the collision between the B-star wind and a relativistic pulsar wind, whereas another centers on a relativistic jet powered by accretion from the Be star decretion disc onto a black hole. Recent high-resolution radio observations showing a putative “cometary tail” pointing away from the Be star near periastron have been cited as support for the pulsar-wind model. Aims. We wish to carry out a quantitative assessment of these competing models. Methods. We apply a “Smoothed Particle Hydrodynamics” (SPH) code in 3D dynamical simulations for both the pulsar-windinteraction and accretion-jet models. The former yields a dynamical description of the shape of the wind-wind interaction surface. The latter provides a dynamical estimation of the accretion rate under a variety of conditions, and how this varies with orbital phase. Results. The results allow critical evaluation of how the two distinct models confront the data in various wavebands. When one accounts for the 3D dynamical wind interaction under realistic constraints for the relative strength of the B-star and pulsar winds, the resulting form of the interaction front does not match the putative “cometary tail” claimed from radio observations. On the other hand, dynamical simulations of the accretion-jet model indicate that the orbital phase variation of accretion power includes a secondary broad peak well away from periastron, thus providing a plausible way to explain the observed TeV gamma ray emission toward apastron. Conclusions. Contrary to previous claims, the colliding-wind model is not clearly established for LS I +61 303, whereas the accretionjet model can reproduce many key characteristics, such as required energy budget, lightcurve, and spectrum of the observed TeV gamma-ray emission.